Perancangan Compact Wardrobe untuk Penari di Gereja, Studi Kasus: Gereja Keluarga Allah Semarang - Pho Hana Amadea Widodo; Adi Santosa (Intra, 2016)
Church’s dancer is a dancer who served on the Christian’s Sunday service. Keluarga Allah Semarang Church’s dancer has a lot of costumes and equipments, but it’s lack of storage containers and the work table making preparation activities can’t used maximally and makes Keluarga Allah Semarang Church’s room look cramped and dirty. Therefore, the designer wants to create a compact wardrobe that not only can help dancers preparation to be more efficient but also can make the room look more compact and tidy. Compact wardrobe was designed by looking the value of aesthetics, ergonomics and functionality. This compact wardrobe concept is compact and efficient. The meaning of ‘compact’ wardrobe is applying the whole dancer’s needs in the room at one wardrobe so that the room looks neater and more concise, while ‘efficient’ concept means to make dancers preparation can be easier. Compact wardrobe can also be used in other church, because the wardrobe is designed with general shapes and colors so it can facilitate other churches that need the compact wardrobe too. The method used by the designer is a qualitative method with direct observations to the location and conducts interviews with 10 dancers from the Keluarga Allah Semarang Church.